2010
DOI: 10.1007/s00015-010-0018-0
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy and palaeoecology of brachiopods from the South-Helvetic zone of the Fäneren region (Lutetian, Eocene, NE Switzerland)

Abstract: Terebratuloid and cancellothyridoid brachiopods from the South-Helvetic Lutetian (Eocene) of the Fäneren region (NE Switzerland) are described: Carneithyris subregularis (QUENSTEDT) and two forms of Terebratulina s.l. under open nomenclature. Several species of Alpine and non-Alpine origin, related to Carneithyris subregularis, like Terebratula kickxi GALEOTTI, Terebratula aequivalvis SCHAFHÄ UTL and Terebratula hilarionis DAVID-SON show characters, which compare well with Carneithyris subregularis. Two of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Transects through the southern Appalachian Mountains, North America, indicate that the topography there has been uplifted and tilted by ∼ 300 m during the last ∼ 40 Ma. These results are a consequence of careful biostratigraphic mapping by Kirkland (1996), Keller et al (2002), Sulser et al (2010) and many others. Citations to primary literature for all points are included in the data tables provided as Supplementary Material.…”
Section: Global Patterns Of Upliftmentioning
confidence: 83%
“…Transects through the southern Appalachian Mountains, North America, indicate that the topography there has been uplifted and tilted by ∼ 300 m during the last ∼ 40 Ma. These results are a consequence of careful biostratigraphic mapping by Kirkland (1996), Keller et al (2002), Sulser et al (2010) and many others. Citations to primary literature for all points are included in the data tables provided as Supplementary Material.…”
Section: Global Patterns Of Upliftmentioning
confidence: 83%
“…To ensure the reliability of the dataset, we checked the bivalve and brachiopod images and corresponding labels. Because the taxonomic system of bivalves and brachiopods is continuously improving ( Konopleva et al, 2017 ; Sulser et al, 2010 ), we categorized the genera whose taxonomic names and positions had been changed in the literature. Additionally, we removed poorly preserved fossil images, which contain two cases.…”
Section: Materials and Datamentioning
confidence: 99%
“…Baeza-Carratalá et al (2014) confirmed that this lithological unit was deposited in a soft-ground environment, with the presence of rounded rhynchonellids and terebratulids thickened in the posterior third of the shell, with very incurved beaks and obliterated or minute pedicle foramina (i.e., absence of a functional pedicle capable of resisting currents; sensu Copper, 1997), which suggested a primarily free-lying life mode for the brachiopod assemblage. The morphological features characterizing these forms were interpreted to provide improved stability in unconsolidated sediments since they allow the shell to turn with prevailing currents (Surlyk, 1972; Álvarez and Emig, 2005; Richardson et al, 2007; Sulser et al, 2010; Baeza-Carratalá et al, 2014).…”
Section: Interpretations On the Habitat And Adaptive Strategies Of CImentioning
confidence: 99%